THE OXYGEN IN THE INTENSIVE TREATMENT AND ANAESTHESIOLOGY – PROS AND CONS? - M. M. Sokolova; V. V. Kuzkov; L. N. Rodionova; M. Yu. Kirov (Вестник анестезиологии и реаниматологии, 2017)
Oxygen is an important component of the critical therapy, however its excessive intake can cause a number of adverse effects. The review describes the benefits and toxic effects of oxygen, as well as its use in the intensive treatment and anesthesiology.